2020
DOI: 10.1016/j.cortex.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic effects of sex hormones and atypical hemispheric asymmetries

Abstract: Functional cerebral asymmetries (FCAs) are a fundamental principle of brain organisation. While specific patterns of asymmetry are characteristic of healthy human brains, atypical or reduced FCAs have been reported for several psychotic disorders, including schizophrenia and mood disorders. However, it is unclear whether atypical FCAs reflect a predisposition to psychotic disorders or a compensatory neural strategy for the progressive structural and functional changes in the brain associated with psychosis. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 249 publications
(321 reference statements)
0
4
0
Order By: Relevance
“…The authors concluded that the appearance of a post-stroke depression is more frequent in women who have suffered an accident in the left hemisphere than in the right. It is possible that gender differences in the consequences of unilateral accidents are partly due to inter-hemispheric differences in physiological endogenous or exogenous conditions, such as those that occur during the ovarian cycle [66,67] or those produced in both genders due to circadian rhythms [reviewed in 67]. On the other hand, it is necessary to take into account that, although there is a hemispheric dominance in brain functions, the left hemisphere for language and the right for visual-spatial functions, both functions are also elaborated, although to a lesser extent, in the contralateral hemisphere [68].…”
Section: Neuropathologies and Brain Asymmetrymentioning
confidence: 99%
“…The authors concluded that the appearance of a post-stroke depression is more frequent in women who have suffered an accident in the left hemisphere than in the right. It is possible that gender differences in the consequences of unilateral accidents are partly due to inter-hemispheric differences in physiological endogenous or exogenous conditions, such as those that occur during the ovarian cycle [66,67] or those produced in both genders due to circadian rhythms [reviewed in 67]. On the other hand, it is necessary to take into account that, although there is a hemispheric dominance in brain functions, the left hemisphere for language and the right for visual-spatial functions, both functions are also elaborated, although to a lesser extent, in the contralateral hemisphere [68].…”
Section: Neuropathologies and Brain Asymmetrymentioning
confidence: 99%
“…The authors attribute much of this effect to the modulation of D2 receptors by estrogen. Moreover, a recent review even argued that estrogen may act as an antipsychotic agent itself, considering that it targets dopamine signaling in a similar way as antipsychotics do [90 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the faster right-sided head growth and subsequent increase of final proportions, there is another assumption for facial asymmetry with left-side deviation–mastication [ 49 ]. Side preference can vary from side to side [ 50 ], but a population trend is noticeable in our sample. Moreover, side preference for the mimic muscles could also affect facial soft-tissue asymmetry [ 33 ].…”
Section: Discussionmentioning
confidence: 90%